Evaluation of the efficiency of the different methods of teaching cardiopulmonary resuscitation to children and adolescents: integrative review - Franco de Oliveira Martins, Laura (2023)
Objective: To evaluate the efficiency of different teaching methods of Basic Life Support for lay students from 12 years of age. Methods: A search was carried out for articles on the MEDLINE/PubMed and Lilacs/BVS platforms between December 2021 and January 2022 to answer the guiding question, "How effective are the different teaching methods of cardiopulmonary resuscitation for children and adolescents?". Articles published in English and Portuguese in the last five years were included. Results: Seven articles addressed teaching methods: self-regulated learning, training of teachers followed by students, peer education, online teaching associated with practical self-training, distance learning, digital training added to practice, and application use through a tablet with subsequent evaluation. In all studies, there was a comparison between intervention and conventional training. In general, all teaching methods contributed to developing the ability to act in trauma situations, but strategies that involved the presence of instructors in training showed better short- and long-term results. Conclusion: this study verified the findings in the literature regarding the effectiveness of different BLS teaching methods for children and adolescents. Among all approaches, better performance was observed in methods that had the presence of instructors, who offered feedback to students and reduced distractions. However, digital, self-regulated, and peer teaching also proved viable. Therefore, the choice of method should be based on the target audience's reality.